Media EduPlay berbantuan Canva untuk meningkatkan numerasi pecahan pada siswa sekolah dasar - Silvia Desanti Lestari; Euis Eti Rohaeti; M. Afrilianto (Curricula: Journal of Curriculum Development, 2026)
The low numeracy skills of Indonesian students, as indicated by the 2022 PISA scores, highlight the need for innovation in Mathematics learning media, especially for simple fractions in elementary schools. This study aims to develop EduPlay media assisted by Canva, based on Problem-Based Learning (PBL), to improve the numeracy skills of third-grade elementary school students in simple fractions. This research was conducted because there is no learning media that integrates Canva, EduPlay gamification, and PBL in a unified manner for fraction learning. The method used is Research and Development (RnD) using the ADDIE model, implemented in March–April 2026. The research subjects consisted of two media experts, one material expert, one education practitioner, and 20 third-grade students in a limited trial. The results showed that the EduPlay media was categorized as very valid and very suitable for use in learning. The limited trial showed that media use improved students' numeracy skills to the moderate category. These findings indicate that the EduPlay media has the potential to support fraction learning in elementary schools.